Retracted Article: Emotional Intelligence And Empathy: Predictors Of Counselors’ General Health - Abomah, Peter Worlanyo; Agbakpe, Gladstone; Quaye, Cynthia Naa Lamiley (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
Emotional intelligence and empathy are important in counseling practice and the counselor's life. The aim of this study was to identify demographic predictors of emotional intelligence, empathy, and general health and determine the predictive relationship between the three variables. In the cross-sectional case study, 133 counselors from Accra Metropolis were administered an online self-report survey consisting of the Emotional Intelligence Questionnaire, Empathy Scale, and General Health Questionnaire. Findings revealed that emotional intelligence and empathy significantly predicted general health (F = 10.159, p<0.01). Other results showed no difference between the general health of male and female counselors (t = 0.470, p>0.05). Additionally, there was no difference in empathy (F=0.887, p>0.05, partial η2=0.021) and emotional intelligence (F = 0.05, p>0.05, partial η2=0.00) between licensed professional counselors and licensed lay counselors. Maintaining the health of counselors is very important because it has an impact on professional competence and on counseling practice. Thus, counselors and training institutions are expected to deepen efforts in creating awareness of the need to protect counselors' health for the benefit of clients and uphold the effectiveness of counselor practice.